Factors Affecting the Profitability of Islamic Commercial Banks for the Period 2018-2022 - Handayani, Pangestika Nur; Widodo, Saniman; Budiyono, Iwan (Kompartemen : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the significance of the effect of the Influence of Third Party Funds (DPK), Musyarakah Financing, Fee Based Income, and Operational Expenses on Operational Revenue (BOPO) towards Return On Asset (ROA) in Sharia Commercial Banks in Indonesia for the period 2018-2022, both simultaneously and partially. The populationn in this study consists of all Sharia Commercial Banks in Indonesia, while the sample used in this study is (eight) Sharia Commercial Banks in Indonesia for the period 2018-2022, selected using purposive sampling technique. The analysis model used in this study is the Multiple Linear Regression Analysis Model, and the analysis techniques include simultaneous significancee testt (F-test), Coefficientt of Determination test (R2), and partial significance test (t-test), processed with SPSS 26.00 program. The results of hypothesis testing and discussion indicate that, partially, Third Party Funds (DPK) have a positive and significant effect on Return on Asset (ROA). Partially, Musyarakah Financing has a negative and significant effect on Return on Asset (ROA). Partially, Fee Based Income has a positive and significant effect on Return on Asset (ROA). Partially, Operational Expenses on Operational Revenue (BOPO) has a negative and significant effect1 on Return on Asset (ROA) in Sharia Commercial Banks in Indonesiaa for the period 2018-2022.